Transitioning from Teaching to Mentoring in Medical Sciences - Amod Gupta (Indian Journal of Radiology and Imaging, 2025)
The transition from traditional teaching to mentoring in medical education is urgently required to create future-ready physicians, researchers, and medical teachers in India. A roadmap was drawn by the pioneers of modern medicine more than 100 years ago, who mentored and prepared the next generation of subspecialists and teachers. We need mentors rather than conventional teachers to inspire students to dream, learn, and grow. In today's world, the role of teachers transcends imparting information to foster critical thinking and contextual application of knowledge. Mentors play a pivotal role in cultivating future medical leaders through recognition, guidance, and mutual respect. Mentors guide lifelong learning and personal development. A trusting mentor–mentee relationship is critical for effective medical education, research, and professional growth. Mentoring significantly benefits residents by fostering well-being, collegiality, and professional skills. Academic mentorship results in increased publication rates, grants, career satisfaction, and retention of faculty in the institutions. With mentors, navigating academia's challenges proves manageable, impacting career trajectory. While mentoring is crucial for career advancement and personal development, there are disparities, especially for women. Formal institutional support for mentoring is essential for sustained impact. Mentor–mentee relationships in academia are evolving toward short-term, need-driven interactions facilitated by workshops during the annual professional society meetings and speed mentoring. E-mentoring offers flexible, cost-effective support transcending geographies and time zones. Identifying the right mentor is crucial for academic success, emphasizing shared knowledge, effective communication, and mutual trust. Evaluating mentoring programs remains challenging, requiring comprehensive, stakeholder-driven assessment tools.